Heart Allograft Tolerance Induced By Hind-Limb Transplant in Rats: Findings of a Pilot Study - Quan Liu; Yong Wang; Atsunori Nakao; Vijay Gorantla; Wensheng Zhang; Xin Xiao Zheng (Research Developments in Medicine and Medical Science Vol. 1, 2023)
The present study shows that a short-term antilymphocyte serum + Cyclosporine A (ALS + CsA) treatment enabled indefinite vascularized hind-limb allograft survival, which induced secondary donor-strain skin and heart allograft tolerance. Transplanting organs or tissues has emerged as a successful treatment for terminal illnesses. Immunosuppression following transplantation, however, may have very negative side effects. To address this issue, donor-specific transplant tolerance was suggested. Here, we describe a novel technique for raising heart allograft tolerance in rats. First, we induced indefinite vascularized hind-limb allograft survival with a short-term antilymphocyte serum + Cyclosporine A treatment. Peripheral blood chimerism disappeared 6-7 weeks after immunosuppression was withdrawn. Then the recipients accepted secondary donor-strain skin and heart transplantation 200 days following vascularized hind-limb transplantation without any immunosuppression, but rejected third party skin allografts, a status of donor-specific tolerance. The ELISPOT results suggested a mechanism of clone deletion. The findings may open new perspectives for the role of vascularized bone transplant, especially vascularized bone marrow transplant, in the induction and maintenance of organ transplantation tolerance.